Comparison of methods of evaluation of breeding lines of soybean (Glycine max Merrill), resistant to stink bugs (Hemiptera:Pentatomidae) - Hoffmann-Campo, Clara Beatriz; Gazzoni, Décio Luiz; Toledo, José Francisco Ferraz de (Pesquisa Agropecuaria Brasileira, 1996)
The methods of soybean planting of short lines, hill seeding with and without protection of a nylon net, were compared to standard 4-line plot, in order to verify the possibility of using the alternative methods to evaluate soybean resistance to stink bugs. Field studies were conducted at the CNPSo/EMBRAPA experimental station (Londrina, Paraná, Brazil), during 1989/90 and 1990/91 soybean seasons, using as indicators for comparison agronomic characteristics, yield and quality of seeds of cultivars and lines, from the maturity groups M, N and O. Results indicated that none of the studied methods presented high correlation with the plot, on all the studied parameters, and for this reason they can not be used for replacing the plot method.